2016
DOI: 10.4028/www.scientific.net/kem.679.59
|View full text |Cite
|
Sign up to set email alerts
|

Research on Deposition Characteristics of the Double-Nozzle in Near-Field Electrospinning

Abstract: With the double-nozzle NFES process, the uncertainty is more suitable to investigate than the multi-nozzle NFES and also meet higher liquid throughput requirement than conventional electrospinning. Moreover, the key point is to control the deposition characteristics of double-nozzle NFES under the interaction of the nozzles. This paper simulates the change in electric field intensity with the change of nozzle length and voltage. The experiment shows that the deposition distance becomes smaller when needle leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…both experimental and computational analysis, highlight that collector distance, nozzle spacing, nozzle length, and applied voltage are the main parameters controlling this electrical crossover. [86,[88][89][90][91][92] In general, the inter-fiber distance deposition increases with an increment in collector distance and nozzle spacing and reduces when needle length increases. In addition, these publications propose several mathematical approaches and computational simulations to understand and predict the multi-nozzle system electrical crossover interference.…”
Section: Pushing the Boundaries Of Ehd Printingmentioning
confidence: 99%
“…both experimental and computational analysis, highlight that collector distance, nozzle spacing, nozzle length, and applied voltage are the main parameters controlling this electrical crossover. [86,[88][89][90][91][92] In general, the inter-fiber distance deposition increases with an increment in collector distance and nozzle spacing and reduces when needle length increases. In addition, these publications propose several mathematical approaches and computational simulations to understand and predict the multi-nozzle system electrical crossover interference.…”
Section: Pushing the Boundaries Of Ehd Printingmentioning
confidence: 99%
“…The mentioned NFES approaches above are all assembled with single nozzle, however, due to the flow restriction, single-nozzle NFES system is unable to cope with mass production, which limits the industrial utilization in precision manufacturing. To improve the high-precision production efficiency and rate, a multinozzle NFES system (Figure ) was presented. On the basis of the mutual influence of the charged jets under shifty conditions, the deposition characteristics of double-nozzle and triple-nozzle NFES systems have been demonstrated and analyzed. The mutual distance of deposition was mainly influenced by nozzle spacing and working distance, on the other hand, the influence of voltage was not particularly apparent, and analysis suggested that the main reason for these phenomena may be the function of Coulomb force.…”
Section: Progress and Mechanism Of Nfesmentioning
confidence: 99%